Art brut : the origins of outsider art / Lucienne Peiry. - Peiry, Lucienne (Flammarion, 2001)
This is the story of the founding of the Art Brut Society, and the lives of the artists whose work the society promoted. Thoroughly documented and illustrated, this study is both exhaustive and compelling.